ADDRESSING THE BILINGUAL TEACHER CRISIS: INVESTING IN SKILLS, SUPPORT, AND INCENTIVES - Xoliqova Xumora Jahongir qizi (Journal of new century innovations, 2024)
Abstract: The bilingual teacher crisis is a pressing issue in many educational systems, with a shortage of qualified bilingual educators exacerbating educational inequities and hindering the academic success of diverse student populations. This article examines the multifaceted nature of the crisis, highlighting the urgent need for comprehensive solutions that address the root causes. It proposes a framework for addressing the crisis through strategic investments in teacher training, professional development, and ongoing support. By creating pathways to increase the number of bilingual teachers and improving their working conditions, this framework aims to empower educators and foster inclusive and equitable learning environments for all students.